2015
DOI: 10.1515/jped-2015-0005
|View full text |Cite
|
Sign up to set email alerts
|

Executive functioning in three groups of pupils in D-KEFS: Selected issues in adapting the test battery for Slovakia

Abstract: The paper reports on the adaptation of a D-KEFS test battery for Slovakia. Drawing on concrete examples, it describes and illustrates the key issues relating to the transfer of test items from one socio-cultural environment to another. The standardisation sample of the population of Slovak pupils in the fourth year of primary school included 250 children with an average age of 9.7 years. The two comparative samples of the same age range were analysed at the same time. They included pupils from classes for gift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
1
8
0
1
Order By: Relevance
“…Several studies suggest that children with weaker executive functions tend to perform poorly on mathematics, at the preschool age [14], and in primary [15], as well as in secondary, education [16]. One study [17] suggested that children with a Roma background in Slovakia did indeed score significantly lower on executive functions than children with a majority background. However, to date, it has not been researched whether an intervention targeting executive functioning would also be effective for the mathematics performance of children with a Roma background.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies suggest that children with weaker executive functions tend to perform poorly on mathematics, at the preschool age [14], and in primary [15], as well as in secondary, education [16]. One study [17] suggested that children with a Roma background in Slovakia did indeed score significantly lower on executive functions than children with a majority background. However, to date, it has not been researched whether an intervention targeting executive functioning would also be effective for the mathematics performance of children with a Roma background.…”
Section: Introductionmentioning
confidence: 99%
“…Dočkal and Filípková [ 10 ] found similar results using a sample of Romani children. Ferjenčík, Slavkovská, and Kresila [ 11 ] stressed the need to develop specific standards for testing the cognitive abilities of Romani children, especially those from culturally disadvantaged backgrounds.…”
Section: Theoretical Foundationsmentioning
confidence: 99%
“…Ferjenčík [ 11 ] also points to the inappropriateness of using a generalized approach for assessing children’s cognitive abilities from culturally disadvantaged backgrounds. Most tests of intelligence and cognitive ability were developed and standardized on the majority population; to be useful for assessing children from culturally disadvantaged backgrounds, these tests need to undergo a thorough adaptation process, and special standards need to be developed.…”
Section: Theoretical Foundationsmentioning
confidence: 99%
“…Porovnanie oboch skupín môžeme raz vidieť v kontexte dosiahnutého hrubého skóre, druhý raz v kontexte noriem vytvorených pre majoritnú populáciu. Prezentované dáta pochádzajú z adaptácie D-KEFS tak, ako sme o nej referovali na inom mieste (Ferjenčík, Slavkovská, & Kresila, 2015).…”
Section: Testové Normy a Minorityunclassified